Entrepreneurship, technology, and income inequality - Metasari Kartika; Erni Panca Kurniasih; Linggar Ikhsan Nugroho (Sebelas Maret Business Review, 2023)
The issue of income inequality between people in the world and Indonesia is still interesting to discuss. Moreover, it is the tenth target in the sustainable development goals until 2030, namely reducing inequality within and between countries. Several targets have also been set, including ensuring equal opportunities and reducing income inequality. The relationship between entrepreneurship, technology, and inequality is studied theoretically and empirically, but empirically there are still not many studies that discuss the relationship between these two variables on income inequality in Indonesia. The research objectives include analyzing the influence of entrepreneurship and technology on income inequality in Indonesia. The data used are from 34 provinces in Indonesia during the period 2013-2020. The data was processed using E-views software. To produce the best model, it will be tested statistically and with classical assumptions. The results showed that entrepreneurship and technology had a significant negative effect on the income inequality variable. Therefore, one solution to overcome income inequality in Indonesia is for the Indonesian government can increase the percentage of individuals or households that can access the Internet.